A hydrophilic fiber dressing for preventing wound adhesion and preparation method thereof
The existing solutions are solved by introducing polarized polyolefin fiber electric field layer, polyacrylic acid 974P nanocellulose absorption layer, acid-base-dependent copolymer indicator layer, oxygen-carrying layer and spray-dried wound layer into the hydrophilic fiber dressing The problems of poor dialysis, poor visibility and negative impact on wounds have achieved the effects of wound oxygen supply, painless debridement and infection monitoring.
Patent Information
- Application Number
- CN202411784496.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing hydrophilic fiber dressings have problems such as poor dialysis, poor visibility, and possible negative effects on the wound during use.
Electric field layer made of polarized polyolefin fibers, absorption layer mixed with 974P polyacrylic acid and nanocellulose, indicator lipid vesicles coated by acid-base-dependent copolymers, oxygen-containing perfluorination in the oxygen-carrying layer Carbon and fibrin gels, as well as wound layers formed by spray drying, combine to form a hydrophilic fiber dressing that prevents wound adhesion.
The dressing can provide wound oxygen supply, enhance wound dialysis, and use indicators to indicate wound healing and infection status, transfer exudate in time to prevent wound adhesion, and achieve painless debridement.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical devices, and in particular to a hydrophilic fiber dressing for preventing wound adhesion and a preparation method thereof. Background Art
[0002] Medical dressings are commonly used medical devices for wound treatment. Their types mainly include traditional fiber dressings, hydrogel dressings, alginate dressings, foam dressings, antibacterial dressings, etc. Among them, the main components of hydrophilic fiber dressings are hydrophilic fibers and some other auxiliary ingredients. Hydrophilic fiber dressings adhere to the wound and the edge of the skin, absorb exudate, and keep the wound moist. In a moist environment, the collagen degrading enzyme in the wound exudate decomposes necrotic substances, which can achieve the effect of autolysis and debridement.
[0003] However, hydrophilic fiber dressings also have the following disadvantages:
[0004] (1) After the dressing covers the wound, it absorbs moisture and has poor permeability, which affects the respiration of wound cells and further affects wound healing, causing the wound to repair more slowly.
[0005] (2) After the dressing is applied to the wound, due to poor visibility, the dressing blocks visual observation and cannot directly reflect the degree of wound healing and wound infection. Especially for burn wounds, the clinical symptoms of infection are very similar to the normal inflammatory response of burns, and the infection of the wound is difficult to grasp, thus hindering effective treatment before the infection expands.
[0006] (3) Wound exudate contains many toxins that are not conducive to wound healing. After the dressing absorbs the wound exudate, it comes into direct contact with the wound surface, which will have a negative impact on the wound surface. Summary of the invention
[0007] The purpose of the present invention is to provide a hydrophilic fiber dressing and a preparation method thereof, which can provide sufficient oxygen supply to the wound surface, visually judge the wound healing status, timely transfer exudate, and prevent wound adhesion. The preparation method of the dressing comprises the following steps:
[0008] S1, preparing an electric field layer: coating polarized polyolefin fibers on a wafer substrate to form a polarized polyolefin fiber layer; coating a metal conductive layer on the polarized polyolefin fiber layer; the metal conductive layer extends outward to form conductive strips to form an electric field layer; the electric field layer includes, from top to bottom, a metal conductive layer, a polarized polyolefin fiber layer, and a wafer substrate;
[0009] S2, preparing an absorption layer: mixing polyacrylic acid 974P and nanocellulose to prepare a mixture A; coating the mixture A on the metal conductive layer to form an absorption layer on the metal conductive layer; the absorption layer is in a loose porous shape;
[0010] S3, preparing a warning layer: using 1,2-distearoyl-sn-phosphocholine, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine, cholesterol, and an indicator to prepare lipid vesicles containing an indicator;
[0011] The indicator is coated with an acid-base dependent copolymer of methyl acrylate-methyl methacrylate-methyl acrylate;
[0012] Spraying lipid vesicles on one side of the absorption layer; spraying methyl acrylate-methyl methacrylate-methyl acrylate coated with an indicator on the other opposite side of the absorption layer to form a warning layer;
[0013] S4, preparing capillaries: preparing a perforation die, the perforation die comprising a bottom plate and a plurality of capillary needle rods, the capillary needle rods being vertically distributed on the bottom plate; using the capillary needle rods of the perforation die to penetrate the warning layer, the absorption layer, and the electric field layer from one side of the warning layer to form capillaries, so that the bottom plate of the perforation die is closely attached to the warning layer;
[0014] S5, preparing an oxygen-carrying layer: dispersing oxygen-containing perfluorocarbon in a fibrinogen solution to prepare a solution B, wherein the oxygen-containing perfluorocarbon is in the form of microspheres in the solution B;
[0015] Solution B and thrombin solution are simultaneously sprayed and condensed on the wafer substrate and the capillary needle rod of the perforation mold, and fibrin gel is formed on the wafer substrate and the capillary needle rod, and oxygen-containing perfluorocarbon microspheres are fixed in the fibrin gel to form an oxygen-carrying layer; the fibrin gel on the surface of the oxygen-carrying layer is in the form of loose pores and capillary columns; the perforation mold is removed to form a hollow capillary column, and the hollow capillary column and the capillary pores together constitute a capillary transmission channel; the capillary transmission channel runs through the warning layer, the absorption layer, the electric field layer, and the oxygen-carrying layer;
[0016] S6, preparing the wound surface layer: adding plasmin and fibronectin to the fibrinogen solution to prepare solution C; then spraying the thrombin solution and solution C onto the oxygen-carrying layer simultaneously by spray drying, so that the thrombin, fibrinogen, plasmin and fibronectin are in the form of dry loose bodies in the oxygen-carrying layer; removing the dry loose bodies at the top of the hollow capillary column to make the capillary transmission channel unobstructed, and preparing the initial dressing product;
[0017] S7, packaging and sterilization: After the initial packaging of the dressing, it is sterilized by gamma ray radiation to form a dressing.
[0018] Polarized polyolefin fiber is a permanently polarized dielectric material. At present, the thermal method and electron bombardment method are mainly used to make the dielectric material undergo a strong potential difference to form a polarized body to prepare polarized polyolefin fiber. The polyolefin sample is heated and cooled to room temperature in turn, while an electric field is applied to the sample to inject space charges into the dielectric material, resulting in dipole arrangement or microscopic charge separation to form a polarized body. This preparation method is called the thermal method.
[0019] The method of using penetrating electron beams to bombard polyolefin polymers to prepare polyolefin fiber polarizers is called electron bombardment. The electron bombardment method can generate high-density initial charges on polyolefin polymers. Usually, within an exposure time of 1 second, a beam energy of 20kev and a beam current of 0.1μa are used to polarize a polyolefin polymer with a thickness of 2μm to 25μm.
[0020] In the medical field, electromagnetic waves are often used to promote bone growth and repair. The inventor unexpectedly discovered in the experiment that the weak electric field provided by polarized polyolefin fibers can promote the healing of skin wounds. Polarized polyolefin fibers are applied to dressings, and the weak electric field provided by polarized polyolefin fibers can promote the healing of skin wounds.
[0021] The wafer substrate in the electric field layer is arranged toward the wound surface. The polarized polyolefin fiber layer provides the electric field, the wafer substrate carries the electric field, and forms a circulation path with the metal conductive layer and the conductive strip to enhance wound repair.
[0022] Polaroids made from polyolefin fibers have extremely high charge stability and can keep the field strength basically constant for several months or even years. Applying polarized polyolefin fibers to dressings can provide a permanent electric field for wounds without the need for an additional power source, extending the effective period of the dressing in terms of the electric field function and facilitating the long-term preservation of the dressing.
[0023] Polarized polyolefin fiber has another advantage, which is that it has good flexibility and can adapt to wound surfaces of different shapes and fit the wound.
[0024] As a preferred embodiment, the thickness of the polarized polyolefin fiber layer is 10 microns to 25 microns.
[0025] As a preferred embodiment, the electric field strength of the polarized polyolefin fiber layer is -3.0×10 -9 Coulomb / square centimeter~-2.0×10 -9 Coulomb / square centimeter. This field strength is very small, comparable to the electrostatic field (ESP) generated by a comb passing through hair. Therefore, at this field strength, no matter how long the exposure time is, it will not cause harmful effects to humans or animals, ensuring the safety of patients.
[0026] As a preferred solution, the metal conductive layer is an aluminum layer, and the thickness of the aluminum layer is 10 microns to 20 microns.
[0027] Polyacrylic acid 974P has a high molecular weight and is usually not absorbed or metabolized in the body. Instead, it is excreted directly through the intestines, similar to the role of dietary fiber. Compared with traditional polyacrylic acid, polyacrylic acid 974P has extremely high safety. Traditional polyacrylic acid is synthesized in benzene, which is a carcinogen. There are strict regulatory restrictions on the use of benzene in pharmaceutical preparations. Polyacrylic acid 974P is synthesized in ethyl acetate, and ethyl acetate is the only residual solvent. Since ethyl acetate has no genotoxicity and no animal carcinogenicity, polyacrylic acid 974P is safer.
[0028] In this application, polyacrylic acid 974P plays a role in increasing the water absorption and moisture retention of the dressing. Compared with traditional polyacrylic acid, polyacrylic acid 974P has a higher viscosity, thus having stronger water absorption and moisture retention. This means that the amount of polyacrylic acid used can be reduced when the same viscosity is produced. This is also one of the reasons why polyacrylic acid 974P is selected for water absorption and moisture retention in this application.
[0029] Radiation sterilization is a commonly used sterilization method for medical devices. However, the inventors found that after radiation sterilization, the viscosity of polyacrylic acid 974P was greatly reduced, and its water absorption and moisture retention properties were greatly reduced. After mixing polyacrylic acid 974P with nanocellulose, the water absorption and moisture retention properties of the gel after radiation can be significantly improved, and the radiation resistance of polyacrylic acid 974P gel can be significantly increased.
[0030] As a preferred embodiment, the mass ratio of the polyacrylic acid 974P to the nanocellulose is 1:3 to 1:10.
[0031] Perfluorocarbon is a colorless, odorless, non-toxic transparent liquid that is insoluble in water, blood, lipids and other media. It has high density, low surface tension, stable chemical properties, and is not metabolized in the body. Perfluorocarbon has a good respiratory gas carrying capacity, and its solubility in oxygen is about 20 times that of water and 2 to 3 times that of whole blood, making it an ideal liquid respiratory medium.
[0032] Oxygenated perfluorocarbons are fixed in fibrin gel to make dressings. During the nursing process, the fibrin gel gradually and slowly hydrolyzes, releasing oxygenated perfluorocarbons, providing an oxygen source for the wound microenvironment, allowing cells to breathe aerobically and promoting wound healing and growth.
[0033] As a preferred embodiment, the content of plasmin in the oxygen-carrying layer gradually decreases from the side facing the wound surface to the opposite side, from 200 mg / ml to 0. Since the content of plasmin on the side facing the wound surface is high, this side hydrolyzes before the opposite side to release oxygen-containing perfluorocarbon. In this case, the oxygen-carrying layer hydrolyzes sequentially from the side facing the wound surface to the opposite side, and an oxygen source can be continuously provided.
[0034] As a preferred embodiment, the oxygen-containing perfluorocarbon is a saturated oxygen-containing perfluorocarbon.
[0035] As a preferred embodiment, the concentration of the thrombin solution used to prepare the oxygen-carrying layer is 500 IU / ml to 2000 IU / ml.
[0036] As a preferred embodiment, the concentration of the fibrinogen solution used to prepare the oxygen-carrying layer is 80 mg / ml to 120 mg / ml.
[0037] When preparing the oxygen-carrying layer, in order to improve the hardness of the hollow capillary column, the protein concentration of the fibrinogen solution can be increased, or the solution can be spray-coagulated and then dried, and this process can be repeated to increase the wall thickness of the hollow capillary column.
[0038] Modern medicine shows that the pH value of the wound can reflect angiogenesis, protease activity and bacterial toxicity during wound healing, and the pH value of the wound plays an important role in the wound healing process. When the pH value is about 5.5, it is slightly acidic, which can promote oxygen perfusion, reduce the presence of bacteria, reduce the proteolytic activity of proteases and enhance fibroblast growth. When the subcutaneous tissue of the skin is injured, bacterial metabolic waste, such as ammonia or toxins, can cause the pH value of the wound to increase to an alkaline level. Poor or non-healing wounds, such as chronic wounds, have an elevated alkaline wound environment with a pH value ranging from 7.1 to 8.2. Therefore, it is meaningful to prepare a dressing that can reflect the pH of the wound microenvironment.
[0039] Methyl acrylate-methyl methacrylate-methyl acrylate copolymer is an acid-base dependent copolymer. When in an acidic environment, it dissolves very slowly; for example, when the pH value is 6, at 20°C, its dissolution rate is less than 0.1 mg / min / g. When in a neutral or alkaline environment, it dissolves faster. For example, when the pH value is 8, at 20°C, its dissolution rate is greater than 10 mg / min / g. Therefore, when the indicator is coated with methyl acrylate-methyl methacrylate-methyl acrylate copolymer, when the pH value reaches 7.1-8.2, the methyl acrylate-methyl methacrylate-methyl acrylate copolymer dissolves quickly and releases the indicator, thereby warning of poor wound healing or even bacterial infection, which attracts the attention of doctors or patients.
[0040] As a preferred embodiment, the indicator is an acid-base indicator, which displays color in a neutral or alkaline environment.
[0041] As a preferred solution, the indicator is a fluorescent indicator which displays color under the irradiation of light waves of a certain wavelength.
[0042] The lipid vesicles contain a fluorescent dye that is released from the vesicles upon contact with a toxin produced by bacteria such as Staphylococcus aureus and / or Pseudomonas aeruginosa, wherein the released dye can be detected by its fluorescence.
[0043] Pseudomonas aeruginosa secretes phospholipases during metabolism. Phospholipases are highly specific and specifically catalyze the degradation of lipids, such as phosphatidylcholine (PC) and phosphatidylethanolamine (PE). Type II lipid vesicles contain 80% 1,2-distearoyl-sn-phosphocholine (DSPC) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE). When the wound is infected by Pseudomonas aeruginosa, Pseudomonas aeruginosa secretes phospholipases to specifically degrade DSPC and DSPE. When DSPC and DSPE are degraded, the indicator in the type II lipid vesicles is released, thereby alerting the wound to infection with Pseudomonas aeruginosa and drawing the attention of doctors or patients. This mechanism may be the reason why type II lipid vesicles are sensitive to Pseudomonas aeruginosa.
[0044] As a preferred embodiment, the mass ratio of DSPC in the lipid vesicles is 78%, the mass ratio of DSPE is 2%, and the mass ratio of cholesterol is 20%.
[0045] Gram-positive Staphylococcus aureus pathogens secrete a variety of protein toxins, including α, γ and δ hemolysins, enterotoxins, etc. Hemolysins can form polymeric pores in the cell membrane, which can non-specifically transport charged ions and charged molecules. During the hemolysis process, the hemolysin pores can interrupt the electrochemical potential gradient on the cell membrane, causing ions to penetrate uncontrolled into and out of the cell, and the cell lyses and dies.
[0046] The free availability of lipid head groups and sufficient fluidity of lipid membranes are necessary conditions for hemolysin monomers to bind to cell membranes. When the number of carbon atoms in the hydrocarbon chain of the lipid bilayer exceeds 14, the lipid bilayer is in a gel state at 37°C, and the hemolysin monomers cannot bind to lipids. In this case, hemolysin cannot destroy the lipid bilayer.
[0047] Type II lipid vesicles are mainly composed of DSPC and DSPE lipids containing 18 carbon atoms in the hydrophobic chain. DSPC and DSPE are almost in a gel state at the experimental temperature of 37°C, and have very low fluidity. Therefore, this prevents the exotoxins secreted by Staphylococcus aureus, such as hemolysin, from binding to the lipid bilayer, and from destroying the structure of type II lipid vesicles, and the indicator in type II lipid vesicles cannot be released. Therefore, when Staphylococcus aureus infects the wound, type II lipid vesicles are stable and cannot give corresponding warnings. This is also the reason why type II lipid vesicles can effectively identify and distinguish Staphylococcus aureus from Pseudomonas aeruginosa, and why type II lipid vesicles are sensitive to Pseudomonas aeruginosa but not to Staphylococcus aureus.
[0048] The mass ratio of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) in type III lipid vesicles is 23%, the mass ratio of 1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (DPPE) is 2%, the mass ratio of cholesterol is 50%, and the mass ratio of 10,12-tricarbonadienoic acid (TCDA) is 25%. Due to the high cholesterol content of type III lipid vesicles, the membrane fluidity is extremely high. Therefore, exotoxins secreted by Staphylococcus aureus, such as hemolysin, can be inserted into the lipid bilayer to form pores, thereby releasing the indicator in the type III lipid vesicles. In addition, cholesterol-rich lipid bilayer membranes are more likely to interact with bacterial toxins such as CBTs. Therefore, the lipid bilayer of type III lipid vesicles is sensitive to Staphylococcus aureus, but not to Pseudomonas aeruginosa.
[0049] On the other hand, most of the lipid degrading enzymes and endotoxins secreted by Pseudomonas aeruginosa require lipids for activation. Since the lipid components of DPPC and DPPE in type III lipid vesicles are minimal, most of the lipid degrading enzymes secreted by Pseudomonas aeruginosa cannot be activated in the lipid membrane mainly composed of cholesterol and TCDA lipids, and cannot degrade the lipid bilayer. Therefore, type III lipid vesicles are insensitive to Pseudomonas aeruginosa. This is also the reason why type III lipid vesicles can effectively identify and distinguish Staphylococcus aureus from Pseudomonas aeruginosa, and why type III lipid vesicles are insensitive to Pseudomonas aeruginosa and sensitive to Staphylococcus aureus.
[0050] As a preferred embodiment, the mass ratio of DPPC in the lipid vesicles is 23%, the mass ratio of DPPE is 2%, the mass ratio of cholesterol is 50%, and the mass ratio of TCDA is 25%.
[0051] By controlling the combined ratio of lipids, cholesterol and polymer lipids, the lipid vesicles showed selective sensitivity between two pathogenic strains, Pseudomonas aeruginosa and Staphylococcus aureus. By integrating the lipid vesicles into wound dressings, this selective sensitivity can quickly indicate the infection status of burn wounds, and the wound healing status can be indirectly observed and diagnosed through indicators, no longer relying on peeling off the wound dressings.
[0052] As a preferred embodiment, the mass ratio of DPPC in the lipid vesicles is 53%, the mass ratio of DPPE is 2%, the mass ratio of cholesterol is 20%, and the mass ratio of TCDA is 25%.
[0053] When the fibrinogen solution does not contain plasmin, the fibrin gel adheres to the wound for a long time; because the animal skin itself can also secrete plasmin, which hydrolyzes the fibrin gel. When the fibrinogen solution contains 5ug / ml to 20ug / ml plasmin, the fibrin gel adheres to the wound for a relatively stable time of 4 to 5 days. When the fibrinogen solution contains 100ug / ml to 200ug / ml plasmin, the fibrin gel adheres to the wound for a shorter time as the plasmin content increases.
[0054] When the fibrin gel is tightly adhered to the wound, removing the dressing will cause damage to the wound and pain to the patient; when the fibrin gel is hydrolyzed, the gel loosens and removing the dressing can avoid wound damage and pain to the patient. Therefore, when the wound is expected to require a shorter nursing time, the plasmin content in the fibrinogen solution can be increased; when the wound is expected to require a longer nursing time, the plasmin content in the fibrinogen solution can be reduced; according to the expected wound nursing time, different concentrations of plasmin can be selectively added to make the fibrin gel adhesion time to the wound basically consistent with the expected nursing time. According to the needs of doctors and patients, choose a dressing with controllable fibrin gel adhesion time to the wound. When the water dressing needs to be removed, the dressing and the wound are also loosened, thereby achieving painless removal and avoiding the defects of ordinary dressings.
[0055] When the thrombin solution and the fibrinogen solution are mixed, a fibrin gel is formed. Depending on the titer concentration of the thrombin solution and the protein concentration of the fibrinogen solution, the fibrin gel formation time varies from 1 second to 5 minutes. The appropriate concentrations of the thrombin solution and the fibrinogen solution can be selected as needed.
[0056] As a preferred embodiment, the fibrinogen solution contains 5 ug / ml to 20 ug / ml plasmin.
[0057] As a preferred embodiment, the titer of the thrombin solution is 500 IU / ml to 2000 IU / ml.
[0058] As a preferred embodiment, the concentration of calcium chloride in the thrombin solution is 60 mmol / L.
[0059] After the fibrinogen solution and the thrombin solution are mixed, a fibrin gel is quickly formed. After the fibrin gel is formed, the fibrin gel is applied to the wound surface, and the adhesion between the fibrin gel and the wound surface is low. By forming a fibrin gel method instantly, the fibrin gel is formed on the wound surface, and the adhesion between the fibrin gel and the wound surface is relatively high. Therefore, thrombin and fibrinogen are generally separated to avoid the formation of fibrin gel before use. The inventors simultaneously dried the fibrinogen solution and the thrombin solution by spray drying to form fibrinogen dry particles and thrombin dry particles, respectively, and the two particles were evenly sprayed on the oxygen-carrying layer to form a wound layer. Since the surface of the oxygen-carrying layer is densely covered with loose pores and capillary columns, the dry particles formed by spray drying can be fully accommodated. Since both fibrinogen and thrombin are in the state of dry particles, the two can exist stably and no gelation reaction will occur. When the wound layer is applied to the wound surface, the wet wound surface dissolves the fibrinogen and thrombin dry particles, and a gelation reaction occurs immediately, so that the dressing is adhered to the wound surface, and the two have a high adhesion.
[0060] When preparing the wound surface layer, due to the uneven height of the hollow capillary columns, the dry particles can cover part of the hollow capillary columns inside the wound surface layer. When the fibrin gel in the wound surface layer is hydrolyzed, this distribution state can quickly transfer the hydrolyzed solution to the absorption layer through capillary action. Some hollow capillary columns can penetrate the wound surface layer, so that the exudate in the early stage of dressing care can be quickly transferred to the absorption layer through the capillary transmission channel by capillary action.
[0061] The second aspect of the present invention provides a hydrophilic fiber dressing for preventing wound adhesion, wherein the dressing is made by the aforementioned preparation method.
[0062] Through the above technical solution, the present invention produces the following beneficial effects:
[0063] (1) Promote the healing of skin wounds through the electric field effect of polarized polyolefin fibers.
[0064] (2) The addition of nanocellulose significantly improved the viscosity, water absorption and moisturizing properties of polyacrylic acid 974P gel after radiation, and significantly increased the radiation resistance of polyacrylic acid 974P gel.
[0065] (3) Fix oxygen-containing perfluorocarbons in fibrin gel. Utilize the characteristics of fibrin gel that gradually and slowly hydrolyzes to continuously release oxygen-containing perfluorocarbons, continuously provide oxygen sources for the wound microenvironment, enable cells to breathe aerobically, and promote wound healing and growth.
[0066] (4) Taking advantage of the fact that the acid-base dependent copolymer methyl acrylate-methyl methacrylate-methyl acrylate dissolves quickly in a neutral or alkaline environment, the indicator is coated with the methyl acrylate-methyl methacrylate-methyl acrylate copolymer. When the wound heals poorly or even has bacterial infection, the methyl acrylate-methyl methacrylate-methyl acrylate copolymer dissolves quickly, releasing the indicator and issuing a warning, thereby attracting the attention of doctors or patients.
[0067] (5) By controlling the composition and combination ratio of lipid vesicles, the lipid vesicles show selective sensitivity between two pathogenic strains, Pseudomonas aeruginosa and Staphylococcus aureus. By utilizing this selective sensitivity, the wound healing status can be indirectly observed and diagnosed through indicators, and the infection status of burn wounds can be quickly indicated without relying on the removal of wound dressings.
[0068] (6) By controlling the plasmin content, the time that fibrin gel adheres to the wound surface is basically consistent with the expected nursing time, and a dressing with controllable fibrin gel adhesion time is prepared, thereby achieving painless debridement.
[0069] (7) Utilize the capillary action of the capillary transmission channel to quickly transfer the wound exudate to the absorption layer and isolate the exudate from the wound.
[0070] (8) Spray drying is used to allow the fibrinogen and thrombin dry particles to coexist stably without affecting each other. When they come into contact with water, they dissolve and undergo a gelation reaction immediately, allowing the dressing to adhere to the wound surface. The two have a high adhesion. DETAILED DESCRIPTION
[0071] In order to make the technical solution of the present invention clearer, the present invention is further described in detail through specific embodiments.
[0072] The specific research process of the present invention is as follows:
[0073] 1. Electric field wound repair test:
[0074] 1. Test method: Under sterile conditions, anesthetized New Zealand rabbits (half male and half female, 1.6-1.8 kg each) were cut with a 1 cm incision on both sides of the lumbar spine, and the incision was full skin thickness. The incision was sutured with sutures. A dressing containing polarized polyolefin fiber was placed on one side of the incision as a test case; a dressing without polarized polyolefin fiber was placed on the other side of the incision as a control case. With this test method, each animal includes a test case and a control case. The dressings were placed in a random manner. The field strength of the dressing containing the polyolefin fiber polarizer is -2.0×10 -9 Coulomb / cm 2 .
[0075] After 72 hours, the skin containing the incision was excised, the sutures were removed, and the samples were subjected to a tensile test using an Instron Tester 1122 tensile tester at a speed of about 200 mm / min.
[0076] 2. Test results and conclusions:
[0077] The tensile test results are as follows: As can be seen from the table, the tensile force of the test example using the polarized polyolefin fiber dressing is significantly higher than that of the dressing without polarized polyolefin fiber, indicating that the polarized polyolefin fiber can accelerate and promote the repair and growth of the wound surface.
[0078]
[0079] 2. Lipid vesicle test:
[0080] 1. Vesicle preparation:
[0081] 1.1 Test materials:
[0082] The lipids used to make vesicles were 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), 1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (DPPE), 1,2-distearoyl-sn-phosphocholine (DSPC), and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE), all purchased from Avanti Polar Lipids.
[0083] 99.99% pure biological grade cholesterol, 10,12-trifluoroacetic acid (TCDA), and 5(6)-carboxyfluorescein were purchased directly from Sigma-Aldrich.
[0084] Cholesterol is a key component of eukaryotic cell membranes, has a significant impact on membrane fluidity, and can interact with bacterial toxins.
[0085] Under partially dehydrated conditions, the lipid bilayer of TCDA (a synthetic polymerizable lipid) was irradiated with UV light to laterally cross-link and stabilize the vesicles.
[0086] 5(6)-Carboxyfluorescein is a fluorescent dye with excitation and emission wavelengths of 495 nm and 520 nm, respectively. It is encapsulated within lipid vesicles. 5(6)-Carboxyfluorescein has been widely used as a tracer in molecular biology and to track cell division, migration, and proliferation in in vitro and in vivo studies. All lipids, cholesterol, and TCDA were used after further purification.
[0087] Triton X-100, purchased from Sigma-Aldrich, is a nonionic detergent that disaggregates lipid vesicles and reduces them to micelles, releasing the encapsulated carboxyfluorescein. It was diluted 10-fold in water and used as a positive control in the plate-reading assay.
[0088] HEPES buffer stabilizing vesicles in the absence of bacteria and Triton X-100 served as a negative control.
[0089] 1.2 Preparation of lipid vesicles:
[0090] (1) Lipids, cholesterol and TCDA were added to chloroform and mixed to a concentration of 100 mmol dm -3 ;
[0091] (2) According to the required ratio of the three lipid vesicles, the above solutions were mixed together to form the required composition, dried under nitrogen, and then placed in 10 -3 bar vacuum chamber for 1 hour to remove solvent residues;
[0092] (3) Dissolve the dried lipid mixture in 5 ml of HEPES buffer at pH 7.3 to make the buffer contain 50 mM dapoxetine. -3 Carboxyfluorescein;
[0093] (4) The buffer was heated in a hot water bath at 75°C for 10 min and then subjected to three repeated cycles of rapid freezing (in liquid nitrogen) and thawing (in a hot water bath);
[0094] (5) The lipid solution was extruded three times through a polycarbonate membrane with a diameter of 100 nm using a Lipofast extruder (Avestin);
[0095] (6) The extruded vesicles were purified by passing through a DNA-grade Sephadex G-25 column (GE Healthcare) in HEPES buffer to separate the vesicles from the unencapsulated carboxyfluorescein dye.
[0096] (7) The lipid vesicles containing TCDA lipids (1 ml each, packed in quartz vials) were stored at 4°C for at least two hours and then irradiated with ultraviolet light (254 nm) for 12 seconds.
[0097] All vesicles were made of 100 mmol dm -3 Freshly prepared lipid stock was made in chloroform at 99.99% purity.
[0098] After preparation, type I lipid vesicles contain 53% DPPC, 2% DPPE, 20% cholesterol and 25% TCDA; type II vesicles contain 78% DSPC, 2% DSPE and 20% cholesterol; type III lipid vesicles contain 23% DPPC, 2% DPPE, 50% cholesterol and 25% TCDA. The mixing ratio of lipid, cholesterol and TCDA in each vesicle is given in mass percentage.
[0099] UV cross-linking was required for type I and type III lipid vesicles because they contained TCDA lipids. After extrusion and UV cross-linking, all vesicles were stored at 4°C until used in experiments.
[0100] 2. Microbial culture:
[0101] 2.1 Microorganisms:
[0102] (1) Gram-positive methicillin-sensitive Staphylococcus aureus (MSSA476) isolated from a clinical setting;
[0103] (2) Gram-negative Pseudomonas aeruginosa (PAOl) strains of clinical significance.
[0104] (3) Laboratory strain (non-pathogenic) Escherichia coli (DH5α), in which most virulence factors were deleted, was used as a control.
[0105] 2.2 Cultivation:
[0106] LB and TSB media for bacterial culture were prepared and sterilized by autoclave before use. DH5a and PAO1 were cultured in LB medium, and MSSA476 was cultured in TSB medium.
[0107] Bacteria were cultured in tubes containing 10 ml of broth and kept in a shaking incubator at 37 °C for 16 h. The optical density (OD) of the cultured bacteria was measured under the following conditions:
[0108] 600 nm in absorbance mode before and after dilution. The OD of the bacteria was then correlated to colony forming units (CFU / ml) by conventional plating and counting methods. The initial concentration of bacteria tested with the vesicles was 10 2 Up to 10 3 CFU / ml range.
[0109] 2.3 Plate reading determination:
[0110] The time-dependent fluorescence response of vesicles during incubation with bacteria growing in was measured using a BMG Labtech Fluorostar plate reader fluorometer with 96-well plates in fluorescence mode with excitation and emission wavelengths of 495 nm and 520 nm, respectively. In a single well, 50ul of each vesicle solution was inoculated with 100ul of diluted broth containing bacteria. The experiment was repeated 6 times for each vesicle type and bacterial combination. 100μg HEPES and diluted Triton X-100 were added to each type of vesicles as negative and positive controls, respectively. The fluorescence response of lipid vesicles inoculated with bacteria, HEPES and Triton X-100 was measured continuously for 20 hours at 37°C. For each type of vesicle and bacterial combination, the average and standard deviation of the fluorescence release measured in 6 replicates were used.
[0111] 3. Test results and analysis:
[0112] The initial bacterial concentration in the broth was 10 2 ~10 3 CFU / ml, it takes an average of 6 hours to observe the fluorescence reaction. As a positive control, Triton X-100 can lyse all vesicles and release fluorescent molecules to the maximum extent. Taking Triton X-100 as a reference and taking its fluorescence intensity as 100%, the fluorescence intensity of other experimental groups was calculated.
[0113] The fluorescence intensity of type I lipid vesicles to PAOl was 79%, and that to MSSA476 was 89.8%. The response of PAOl was slightly lower than that of MSSA476. Type I lipid vesicles had obvious responses to both PAOl and MSSA476, indicating that they were sensitive to both PAOl and MSSA476.
[0114] The fluorescence intensity of type I lipid vesicles to HEPES and DH5a was very low, which was very different from the fluorescence intensity of PAO1 and MSSA476. This indicated that type I lipid vesicles were sensitive to pathogenic PAO 1 and MSSA476, but not to non-pathogenic E. coli DH5α.
[0115]
[0116] The fluorescence intensity of type II lipid vesicles to PAOl was 74.5%, and to MSSA476 was less than 13.9%, so the sensitivity to PAOl was 5 times that of MSSA476. When the fluorescence intensity was less than 15%, it was difficult to detect, so there was a clear difference in fluorescence intensity between the wells containing PAOl and the wells containing MSSA476.
[0117] The toxins produced by Pseudomonas aeruginosa are mostly lipid-degrading exoenzymes, such as phospholipases, in addition to endotoxins associated with the outer cell membrane of Gram-negative bacteria. Bacterial phospholipases have strong site specificity and are known to target major lipids of eukaryotic cell membranes, including phosphatidylcholine (PC) and phosphatidylethanolamine (PE). Bacterial phospholipases specifically recognize target lipids and are able to hydrolyze them through catalytic action. Type II lipid vesicles contain 80% DSPC and DSPE, which become the main targets of PAOl exoenzyme toxins. This mechanism may underlie the sensitivity of type II lipid vesicles to PAOl.
[0118] Gram-positive Staphylococcus aureus pathogens secrete a variety of toxins, including α, γ, and δ hemolysins, enterotoxins, leukocytic acid, and toxic shock syndrome toxin (TSST). Hemolysins are pore-forming toxins (PFTs) that form heptamer pores in cell membranes that have an affinity for the transport of ions and charged molecules and are non-specific. During the hemolysis of cell membranes in vivo, the hemolysin pores interrupt the electrochemical potential gradient on the cell membrane, resulting in uncontrolled permeation of ions into and out of the cell, and cell death due to lysis. The binding of hemolysin monomers to the cell membrane requires the free availability of lipid head groups and sufficient fluidity of the lipid membrane. The lipid bilayer composed of lipids with more than 14 carbon atoms in the hydrocarbon chain is in a gel state at 37°C, so it is not sufficient for hemolysin insertion and cannot provide free lipid head groups for hemolysin to bind. Type II vesicles are mainly composed of DSPC and DSPE lipids with 18 carbon atom hydrophobic chains, so the lipid bilayer is almost in a gel state at 37°C with limited fluidity. In this case, the exotoxin MSSA476 cannot penetrate the lipid bilayer. Therefore, in the presence of MSSA476, type II vesicles are relatively stable. Therefore, type II vesicles are insensitive to MSSA476.
[0119] The mass ratio of DPPC in type III lipid vesicles is 23%, the mass ratio of DPPE is 2%, the mass ratio of cholesterol is 50%, and the mass ratio of TCDA is 25%. Due to the high cholesterol content of type III lipid vesicles, the membrane fluidity is extremely high. Therefore, exotoxins secreted by Staphylococcus aureus, such as hemolysin, can be inserted into the lipid bilayer to form pores, thereby releasing the indicator in the type III lipid vesicles. In addition, the cholesterol-rich lipid bilayer membrane is more likely to interact with bacterial toxins such as CBTs. Therefore, the lipid bilayer of type III lipid vesicles is sensitive to Staphylococcus aureus, but not to Pseudomonas aeruginosa.
[0120] On the other hand, most of the lipid degrading enzymes and endotoxins secreted by Pseudomonas aeruginosa require lipids for activation. Since the lipid components of DPPC and DPPE in type III lipid vesicles are minimal, most of the lipid degrading enzymes secreted by Pseudomonas aeruginosa cannot be activated in the lipid membrane mainly composed of cholesterol and TCDA lipids, and cannot degrade the lipid bilayer. Therefore, type III lipid vesicles are insensitive to Pseudomonas aeruginosa. This is also the reason why type III lipid vesicles can effectively identify and distinguish Staphylococcus aureus from Pseudomonas aeruginosa, and why type III lipid vesicles are insensitive to Pseudomonas aeruginosa and sensitive to Staphylococcus aureus.
[0121] All types of vesicles showed no fluorescent response in HEPES and E. coli DH5a, indicating that all vesicles tested in this experiment had clear visual distinction between pathogenic and non-pathogenic bacteria and had effective selectivity, especially between the non-pathogenic E. coli DH5α and the pathogenic Staphylococcus aureus MSSA476 and PAO1.
[0122] By selecting the combination and concentration of lipids, cholesterol and polymer lipids, the vesicles showed selective sensitivity between two pathogenic strains, PAO1 and MSSA476. By integrating lipid vesicles into wound dressings, the current selective and discriminatory sensing system can be used as a rapid indicator of burn wound infection, diagnosing and judging wound healing without relying on removing wound dressings.
[0123] 3. Fibrin gel hydrolysis test:
[0124] After thrombin acts on fibrinogen, fibrin gel is quickly formed and adheres to the wound surface. Fibrin gel can be hydrolyzed and absorbed, and has good biocompatibility. Its absorption rate is directly related to the content of plasmin. The purpose of this test is to confirm the correlation between the content of plasmin and the hydrolysis of fibrin gel.
[0125] 1. Test method:
[0126] Prepare thrombin solution with a titer of 500 IU / ml;
[0127] Prepare fibrinogen solution 1 with a protein concentration of 100 mg / ml and without plasmin;
[0128] Prepare fibrinogen solution 2 with a protein concentration of 100 mg / ml and a plasmin content of 5 ug / ml;
[0129] Prepare fibrinogen solution 3, with a protein concentration of 100 mg / ml and a plasmin content of 20 ug / ml;
[0130] Prepare fibrinogen solution 3, with a protein concentration of 100 mg / ml and a plasmin content of 100 ug / ml;
[0131] Prepare fibrinogen solution 3, with a protein concentration of 100 mg / ml and a plasmin content of 200 ug / ml;
[0132] 50uL of thrombin solution was mixed with 50uL of each of fibrinogen solutions 1 to 5 in equal volumes and sprayed on 1 cm2 of the wound surface of pig skin to form fibrin gel. The hydrolysis of the fibrin gel was observed and recorded.
[0133] 2. Test results and analysis:
[0134] The hydrolysis of fibrin gel is shown in the table below.
[0135]
[0136] When the fibrinogen solution does not contain plasmin, the fibrin gel adheres to the wound for a longer time; since the animal skin itself also secretes plasmin, it hydrolyzes the fibrin gel.
[0137] When the fibrinogen solution contains 5ug / ml to 20ug / ml plasmin, the fibrin gel adheres to the wound for a relatively stable period of 4 to 5 days.
[0138] When the fibrinogen solution contains 100ug / ml to 200ug / ml plasmin, the time that the fibrin gel adheres to the wound surface shortens as the plasmin content increases.
[0139] The experimental results provide the following inspiration: when the wound requires a shorter care time, the plasmin content in the fibrinogen solution can be increased; when the wound requires a longer care time, the plasmin content in the fibrinogen solution can be reduced; based on the experimental results, the time that fibrin gel adheres to the wound can be controlled.
[0140] When the fibrin gel is tightly adhered to the wound surface, removing the dressing will cause damage to the wound surface and cause pain to the patient; when the fibrin gel is hydrolyzed, the gel loosens and removing the dressing can avoid damaging the wound surface and causing pain to the patient; therefore, according to the needs of doctors and patients, dressings with controllable fibrin gel adhesion time can be selected to avoid the pain caused by peeling off the dressing from the wound.
[0141] 4. Effect of nanocellulose on the viscosity of gel before and after radiation sterilization:
[0142] In this test, % are all mass ratios.
[0143] 1. Test method:
[0144] Test 1 Sample preparation: Weigh polyacrylic acid 974P and disperse it in pure water, mix well to produce a gelled dispersion, use 20% potassium hydroxide solution to adjust the pH of the dispersion to 6.2, and then quantify it with pure water to make the concentration of polyacrylic acid 974P reach 1.0%, and then degas the gel.
[0145] Test 2 Sample preparation: Weigh polyacrylic acid 974P and disperse it in pure water, mix well to produce a gelled dispersion, use 20% potassium hydroxide solution to adjust the pH of the dispersion to 6.2, weigh nanocellulose and disperse it in the dispersion, and then quantify it with pure water to make the concentration of polyacrylic acid 974P reach 1.0%, and the concentration of nanocellulose reach 3%, and then degas the gel.
[0146] Sample preparation for experiment 3: Weigh polyacrylic acid 974P and disperse it in pure water, mix well to produce a gelled dispersion, use 20% potassium hydroxide solution to adjust the pH of the dispersion to 6.2, weigh nanocellulose and disperse it in the dispersion, and then quantify it with pure water to make the concentration of polyacrylic acid 974P reach 1.0%, and the concentration of nanocellulose reach 5%, and then degas the gel.
[0147] Test 4 Sample preparation: Weigh polyacrylic acid 974P and disperse it in pure water, mix well to produce a gelled dispersion, use 20% potassium hydroxide solution to adjust the pH of the dispersion to 6.2, weigh nanocellulose and disperse it in the dispersion, and then quantify it with pure water to make the concentration of polyacrylic acid 974P reach 1.0%, and the concentration of nanocellulose reach 10%, and then degas the gel.
[0148] The samples were sterilized by gamma ray radiation at a dose of 45 kGy, and the gel viscosity was measured using a Brookfield™ viscometer LVF.
[0149] 2. Test results and analysis:
[0150] The experimental results show that compared with the gel without adding nanocellulose, the viscosity decrease rate of the sample after radiation is significantly reduced after adding nanocellulose. Nanocellulose can significantly increase the viscosity of the gel after radiation and significantly increase the anti-radiation performance of the gel.
[0151]
[0152] Based on the previous research, the applicant conducted verification by preparing dressings.
[0153] Example 1
[0154] The hydrophilic fiber dressing for preventing wound adhesion is prepared by the following steps:
[0155] S1, preparation of electric field layer:
[0156] The polarized polyolefin fiber body is coated on a wafer substrate to form a polarized polyolefin fiber layer; an aluminum conductive layer is coated on the polarized polyolefin fiber layer; the aluminum conductive layer extends outward to form a conductive strip to form an electric field layer; the electric field layer includes an aluminum conductive layer, a polarized polyolefin fiber layer, and a wafer substrate in order from top to bottom; the thickness of the polarized polyolefin fiber body layer is 10 microns; the electric field strength of the polarized polyolefin fiber body layer is -3.0×10 -9 Coulomb / square centimeter; the thickness of the aluminum conductive layer is 10 microns;
[0157] S2, preparation of absorption layer:
[0158] Mixing polyacrylic acid 974P and nanocellulose to prepare mixture A; the mass ratio of polyacrylic acid 974P to nanocellulose is 1:3; coating mixture A on the aluminum conductive layer to form an absorption layer on the aluminum conductive layer; the absorption layer is in a loose porous shape; the thickness of the absorption layer is 1 mm;
[0159] S3, preparing a warning layer:
[0160] Lipid vesicles containing carboxyfluorescein were prepared using 1,2-distearoyl-sn-phosphocholine, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine, cholesterol and carboxyfluorescein; the mass ratio of DSPC in the lipid vesicles was 78%, the mass ratio of DSPE was 2%, and the mass ratio of cholesterol was 20%;
[0161] Carboxyfluorescein was encapsulated using an acid-base dependent copolymer, methyl acrylate-methyl methacrylate-methyl acrylate;
[0162] Spray the lipid vesicles on the left side of the absorption layer; spray the coated carboxyfluorescein on the right side of the absorption layer to form a warning layer;
[0163] S4, preparing capillaries:
[0164] Prepare a perforation die, which includes a bottom plate and capillary needle rods, wherein the capillary needle rods are vertically and densely distributed on the bottom plate, and the height of the capillary needle rods is 6 mm;
[0165] Use the capillary needle rod of the perforating die to penetrate the warning layer, the absorption layer, and the electric field layer on one side of the warning layer to form capillary holes, so that the bottom plate of the perforating die is closely attached to the warning layer;
[0166] S5, preparing the oxygen-carrying layer:
[0167] Saturated oxygen perfluorocarbon is dispersed in a fibrinogen solution to prepare a solution B, in which the saturated oxygen perfluorocarbon is in the form of microspheres; the volume ratio of the saturated oxygen perfluorocarbon to the fibrinogen solution is 0.3:1; the protein content of the fibrinogen solution is 80 mg / ml;
[0168] Solution B and thrombin solution are sprayed and condensed on the wafer substrate and the capillary needle rod of the perforation mold at the same time to form fibrin gel, and saturated oxygen perfluorocarbon microspheres are fixed in the fibrin gel to form an oxygen-carrying layer; the fibrin gel on the surface of the oxygen-carrying layer is densely covered with loose pores and hollow capillary columns; the height distribution of the hollow capillary columns is 0-1 mm; the perforation mold is removed, and the hollow capillary columns and capillary pores together form a capillary transmission channel; the capillary transmission channel runs through the warning layer, the absorption layer, the electric field layer, and the oxygen-carrying layer; the thickness of the oxygen-carrying layer is 4 mm; the potency of the thrombin solution is 500 IU / ml;
[0169] S6, preparation of wound surface layer:
[0170] Plasmin and fibronectin are added to the fibrinogen solution to prepare solution C; solution C contains 5ug / ml plasmin; solution C contains 8mg / ml fibronectin; the protein content of the fibrinogen solution is 80mg / ml;
[0171] Then, the thrombin solution and solution C are sprayed on the oxygen-carrying layer simultaneously by spray drying, and thrombin, fibrinogen, plasmin, and fibronectin are in the form of dry loose bodies in the oxygen-carrying layer; the potency of the thrombin solution is 500 IU / ml;
[0172] Cut the hollow capillary column at 1 mm in height, remove some of the dry loose bodies at the top of the hollow capillary column, so that the capillary transmission channel is unblocked, and prepare the initial dressing; cut the initial dressing into small pieces of 3 cm×3 cm;
[0173] S7, Packaging, Sterilization:
[0174] A transparent dialysis bandage is arranged on the small warning layer to fix the dressing on a specific wound surface, and then the dressing is packaged and sterilized by gamma ray radiation at a dose of 45 kGy to form a dressing. Each layer of the dressing contains an antibacterial agent.
[0175] Example 2
[0176] The hydrophilic fiber dressing for preventing wound adhesion is prepared by the following steps:
[0177] S1, preparation of electric field layer:
[0178] The polyolefin fiber polarizer is coated on a wafer substrate to form a polarized polyolefin fiber layer; an aluminum conductive layer is coated on the polarized polyolefin fiber layer; the aluminum conductive layer extends outward to form a conductive strip to form an electric field layer; the electric field layer includes an aluminum conductive layer, a polarized polyolefin fiber layer, and a wafer substrate in order from top to bottom; the thickness of the polarized polyolefin fiber layer is 15 microns; the electric field strength of the polarized polyolefin fiber layer is -2.5×10 -9 Coulomb / square centimeter; the thickness of the aluminum conductive layer is 15 microns;
[0179] S2, preparation of absorption layer:
[0180] Mixing polyacrylic acid 974P and nanocellulose to prepare mixture A; the mass ratio of polyacrylic acid 974P to nanocellulose is 1:6; coating mixture A on the aluminum conductive layer to form an absorption layer on the aluminum conductive layer; the absorption layer is in a loose porous shape; the thickness of the absorption layer is 2 mm;
[0181] S3, preparing a warning layer:
[0182] Lipid vesicles containing carboxyfluorescein were prepared using 1,2-distearoyl-sn-phosphocholine, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine, cholesterol and carboxyfluorescein; the mass ratio of DPPC in the lipid vesicles was 23%, the mass ratio of DPPE was 2%, the mass ratio of cholesterol was 50%, and the mass ratio of TCDA was 25%;
[0183] Carboxyfluorescein was encapsulated using an acid-base dependent copolymer, methyl acrylate-methyl methacrylate-methyl acrylate;
[0184] Spray the lipid vesicles on the left side of the absorption layer; spray the coated carboxyfluorescein on the right side of the absorption layer to form a warning layer;
[0185] S4, preparing capillaries:
[0186] Prepare a perforation die, which includes a bottom plate and capillary needle rods, the capillary needle rods are vertically and densely distributed on the bottom plate, and the height of the capillary needle rods is 8 mm;
[0187] Use the capillary needle rod of the perforating die to penetrate the warning layer, the absorption layer, and the electric field layer on one side of the warning layer to form capillary holes, so that the bottom plate of the perforating die is closely attached to the warning layer;
[0188] S5, preparing the oxygen-carrying layer:
[0189] Saturated oxygen perfluorocarbon is dispersed in a fibrinogen solution to prepare a solution B, in which the saturated oxygen perfluorocarbon is in the form of microspheres; the volume ratio of the saturated oxygen perfluorocarbon to the fibrinogen solution is 0.6:1; the protein content of the fibrinogen solution is 1000 mg / ml;
[0190] Solution B and thrombin solution are simultaneously sprayed and condensed on the wafer substrate and the capillary needle rod of the perforation mold to form a fibrin gel, and saturated oxygen perfluorocarbon microspheres are fixed in the fibrin gel to form an oxygen-carrying layer; the fibrin gel on the surface of the oxygen-carrying layer is densely covered with loose pores and hollow capillary columns; the height distribution of the hollow capillary columns is 0-2 mm; the perforation mold is removed, and the hollow capillary columns and the capillary pores together form a capillary transmission channel; the capillary transmission channel runs through the warning layer, the absorption layer, the electric field layer, and the oxygen-carrying layer; the thickness of the oxygen-carrying layer is 4 mm; the potency of the thrombin solution is 1000 IU / ml;
[0191] S6, preparation of wound surface layer:
[0192] Plasmin and fibronectin were added to the fibrinogen solution to prepare solution C; solution C contained 10 ug / ml plasmin; solution C contained 10 mg / ml fibronectin; the protein content of the fibrinogen solution was 100 mg / ml;
[0193] Then, the thrombin solution and solution C are sprayed on the oxygen-carrying layer simultaneously by spray drying, and thrombin, fibrinogen, plasmin, and fibronectin are in the form of dry loose bodies in the oxygen-carrying layer; the potency of the thrombin solution is 1000 IU / ml;
[0194] Cut the hollow capillary column at 2 mm in height, remove some of the dry loose bodies at the top of the hollow capillary column, so that the capillary transmission channel is unblocked, and prepare the initial dressing; cut the initial dressing into small pieces of 3 cm×3 cm;
[0195] S7, Packaging, Sterilization:
[0196] A transparent dialysis bandage is arranged on the small warning layer to fix the dressing on a specific wound surface, and then the dressing is packaged and sterilized by gamma ray radiation at a dose of 45 kGy to form a dressing. Each layer of the dressing contains an antibacterial agent.
[0197] Example 3
[0198] The hydrophilic fiber dressing for preventing wound adhesion is prepared by the following steps:
[0199] S1, preparation of electric field layer:
[0200] The polarized polyolefin fiber body is coated on a wafer substrate to form a polarized polyolefin fiber layer; an aluminum conductive layer is coated on the polarized polyolefin fiber layer; the aluminum conductive layer extends outward to form a conductive strip to form an electric field layer; the electric field layer includes an aluminum conductive layer, a polarized polyolefin fiber layer, and a wafer substrate in order from top to bottom; the thickness of the polarized polyolefin fiber body layer is 25 microns; the electric field strength of the polarized polyolefin fiber body layer is -2.0×10 -9 Coulomb / square centimeter; the thickness of the aluminum conductive layer is 20 microns;
[0201] S2, preparation of absorption layer:
[0202] Mixing polyacrylic acid 974P and nanocellulose to prepare mixture A; the mass ratio of polyacrylic acid 974P to nanocellulose is 1:10; coating mixture A on the aluminum conductive layer to form an absorption layer on the aluminum conductive layer; the absorption layer is in a loose porous shape; the thickness of the absorption layer is 3 mm;
[0203] S3, preparing a warning layer:
[0204] Lipid vesicles containing carboxyfluorescein were prepared using 1,2-distearoyl-sn-phosphocholine, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine, cholesterol and carboxyfluorescein; the mass ratio of DPPC in the lipid vesicles was 53%, the mass ratio of DPPE was 2%, the mass ratio of cholesterol was 20%, and the mass ratio of TCDA was 25%;
[0205] Carboxyfluorescein was encapsulated using an acid-base dependent copolymer, methyl acrylate-methyl methacrylate-methyl acrylate;
[0206] Spray the lipid vesicles on the left side of the absorption layer; spray the coated carboxyfluorescein on the right side of the absorption layer to form a warning layer;
[0207] S4, preparing capillaries:
[0208] Prepare a perforation die, which includes a bottom plate and capillary needle rods, wherein the capillary needle rods are vertically and densely distributed on the bottom plate, and the height of the capillary needle rods is 12 mm;
[0209] Use the capillary needle rod of the perforating die to penetrate the warning layer, the absorption layer, and the electric field layer on one side of the warning layer to form capillary holes, so that the bottom plate of the perforating die is closely attached to the warning layer;
[0210] S5, preparing the oxygen-carrying layer:
[0211] Saturated oxygen perfluorocarbon is dispersed in a fibrinogen solution to prepare a solution B, in which the saturated oxygen perfluorocarbon is in the form of microspheres; the volume ratio of the saturated oxygen perfluorocarbon to the fibrinogen solution is 1:1; the protein content of the fibrinogen solution is 120 mg / ml;
[0212] Solution B and thrombin solution are simultaneously sprayed and condensed on the wafer substrate and the capillary needle rod of the perforation mold to form a fibrin gel, and saturated oxygen perfluorocarbon microspheres are fixed in the fibrin gel to form an oxygen-carrying layer; the fibrin gel on the surface of the oxygen-carrying layer is densely covered with loose pores and hollow capillary columns; the height distribution of the hollow capillary columns is 0-3 mm; the perforation mold is removed, and the hollow capillary columns and the capillary pores together form a capillary transmission channel; the capillary transmission channel runs through the warning layer, the absorption layer, the electric field layer, and the oxygen-carrying layer; the thickness of the oxygen-carrying layer is 6 mm; the potency of the thrombin solution is 2000 IU / ml;
[0213] S6, preparation of wound surface layer:
[0214] Plasmin and fibronectin were added to the fibrinogen solution to prepare solution C; solution C contained 20 ug / ml plasmin; solution C contained 12 mg / ml fibronectin; the protein content of the fibrinogen solution was 120 mg / ml;
[0215] Then, the thrombin solution and solution C are sprayed on the oxygen-carrying layer simultaneously by spray drying, and thrombin, fibrinogen, plasmin, and fibronectin are in the form of dry loose bodies in the oxygen-carrying layer; the potency of the thrombin solution is 2000 IU / ml;
[0216] Cut the hollow capillary column at 3 mm in height, remove some of the dry loose bodies at the top of the hollow capillary column, so that the capillary transmission channel is unblocked, and prepare the initial dressing; cut the initial dressing into small pieces of 3 cm×3 cm;
[0217] S7, Packaging, Sterilization:
[0218] A transparent dialysis bandage is arranged on the small warning layer to fix the dressing on a specific wound surface, and then the dressing is packaged and sterilized by gamma ray radiation at a dose of 45 kGy to form a dressing. Each layer of the dressing contains an antibacterial agent.
[0219] Test Example 1, Cytotoxicity and Debridement Effect:
[0220] The cytotoxicity and debridement effects of the samples prepared in Examples 1 to 3 were tested and evaluated.
[0221] 1. Cytotoxicity:
[0222] 1.1 Test method: The test was conducted in accordance with the MTT method in GB / T 16886.5-2017 Biological evaluation of medical devices Part 5: In vitro cytotoxicity test method.
[0223] 1.2 Test results and analysis: The cell viability of the samples prepared in Examples 1 to 3 was greater than ≥80%, which met the national standard requirements (≥70%), indicating that the dressing prepared by the technical solution of the present invention has good biocompatibility.
[0224] 2. Debridement effect:
[0225] 2.1 Test method:
[0226] A 2 mm skin biopsy device was used to create a 2 mm diameter full-thickness skin defect wound on fresh pig skin. The wound was 2 mm in diameter and 2 mm in height, and one side was cut open at 45 degrees at the lower end.
[0227] Place the full-thickness skin defect wound in a 37°C constant temperature box for 30 minutes to equilibrate it to 37°C. Take it out and apply the dressing on the wound. After nursing the wound for a period of time, when the dressing and the wound are loose, remove the dressing and rinse with sterile saline.
[0228] 2.2 Test results and analysis: After the dressing care of Example 1, Example 2, and Example 3 was completed, the dressing was removed, and the wound surface was rinsed with sterile saline, and the necrotic tissue and contaminants were rinsed away without the need for any surgical instrument operation.
[0229] Test Example 2, warning test:
[0230] A total of 90 patients with first-degree skin burns were recruited for the trial.
[0231] The dressing of Example 1 was used to care for 30 patients with skin burns. The dressings of 3 of the patients showed green fluorescence on the right side of the warning layer under the irradiation of the excitation wave; after inspection in the nursing laboratory, it was confirmed that their wounds healed poorly. The dressing of 1 patient showed green fluorescence on the left side of the warning layer under the irradiation of the excitation wave; after inspection in the nursing laboratory, it was confirmed that the wound was infected with Pseudomonas aeruginosa. The dressing of 1 patient showed green fluorescence on both sides of the warning layer under the irradiation of the excitation wave; after inspection in the nursing laboratory, it was confirmed that the wound was infected with Pseudomonas aeruginosa and had poor healing.
[0232] The dressing of Example 2 was used to care for 30 patients with skin burns. The dressings of 6 patients showed green fluorescence on the right side of the warning layer under the irradiation of the excitation wave; after inspection in the nursing laboratory, it was confirmed that the wound healing was poor. The dressing of 1 patient showed green fluorescence on the left side of the warning layer under the irradiation of the excitation wave; after inspection in the nursing laboratory, it was confirmed that the wound was infected with Staphylococcus aureus.
[0233] The dressing of Example 3 was used to care for 30 patients with skin burns. The dressings of 2 patients showed green fluorescence on the right side of the warning layer under the irradiation of the excitation wave; the nursing laboratory examination confirmed that their wounds healed poorly. The dressings of 2 patients showed green fluorescence on the left side of the warning layer under the irradiation of the excitation wave; the laboratory examination confirmed that their wounds were infected with Staphylococcus aureus.
[0234] The above test results show that the dressings of Example 1, Example 2, and Example 3 can accurately indicate the wound healing and infection conditions, and issue timely warnings for nursing.
[0235] Test Example 3, hydrolysis test:
[0236] 90 patients with first-degree skin burns, exactly the same as Test Case 2.
[0237] Use dressings to care for patients' burned skin, and observe and record the loosening time of the dressing and the wound, that is, the duration of adhesion between the dressing and the wound.
[0238] The dressing of Example 1 was used to care for 30 patients with skin burns, and the average duration of adhesion between the dressing and the wound surface was 111 h±13 h.
[0239] The dressing of Example 2 was used to care for 30 patients with skin burns, and the average duration of adhesion between the dressing and the wound surface was 102 h±12 h.
[0240] The dressing of Example 3 was used to care for 30 patients with skin burns, and the average duration of adhesion between the dressing and the wound surface was 94 h±9 h.
[0241] After the dressing and wound surface were loosened, 90 patients felt no pain when removing the dressing, and the painless debridement was experimentally performed by flushing with sterile saline after removal.
[0242] As the content of plasmin in the dressings of Examples 1 to 3 gradually increases, the adhesion time between the dressings of Examples 1 to 3 and the wound surface gradually shortens, which is basically consistent with the experimental phenomenon in the research process. According to this phenomenon, the content of plasmin can be selectively added based on the estimated nursing time, so that the duration of adhesion between the dressing and the wound surface is basically consistent with the expected nursing time, and when the dressing needs to be removed, the dressing and the wound surface loosen, thereby achieving painless removal.
[0243] Test Example 4, exudate transfer test:
[0244] 90 patients with first-degree skin burns, exactly the same as Test Case 2.
[0245] The patients' burnt skin was cared for using dressings, and the transfer of exudate was observed and recorded. Among the 90 patients, 88 cases were able to transfer the exudate to the absorption layer in time, while 2 cases could not transfer the exudate in time due to the blockage of capillary transmission channels caused by the large amount of foreign matter on the wound surface.
[0246] Test Example 5, wound healing test:
[0247] 90 patients with first-degree skin burns, exactly the same as Test Case 2.
[0248] Use dressings to care for patients' burned skin and observe and record wound healing.
[0249] Among the 90 patients, the average wound recovery time was 4 days ± 2 days.
[0250] While test case 5 was being conducted, a comparative test of a similar product (hydrophilic fiber dressing) was also carried out, involving a total of 30 patients, with an average wound recovery time of 6 days ± 4 days.
[0251] The wound healing and repair speed of the dressings prepared in Example 1, Example 2, and Example 3 is significantly faster than that of similar products. The main reasons may be as follows:
[0252] (1) The dressing of the present invention contains an electric field layer, which continuously accelerates wound healing through the electric field;
[0253] (2) The fibrin gel and fibronectin contained in the dressing of the present invention can promote cell growth and accelerate wound healing;
[0254] (3) The dressing of the present invention can continuously provide an oxygen source, create conditions for cellular aerobic respiration, and accelerate wound healing;
[0255] (4) The dressing of the present invention can timely transfer wound exudate away from the wound surface and promote wound healing.
[0256] Therefore, under the care of the dressing of the present invention, the wound heals faster. However, ordinary glue dressings only have absorption and moisturizing functions and have no obvious promoting effect on the growth of wound cells.
[0257] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a hydrophilic fiber dressing for preventing wound adhesion, characterized in that: The following steps are involved: S1, preparing an electric field layer: coating polarized polyolefin fibers on a wafer substrate to form a polarized polyolefin fiber layer; coating a metal conductive layer on the polarized polyolefin fiber layer; the metal conductive layer extends outward to form conductive strips to form an electric field layer; the electric field layer includes, from top to bottom, a metal conductive layer, a polarized polyolefin fiber layer, and a wafer substrate; S2, preparing an absorption layer: mixing polyacrylic acid 974P and nanocellulose to prepare a mixture A; coating the mixture A on the metal conductive layer to form an absorption layer on the metal conductive layer; the absorption layer is in a loose porous shape; S3, preparing a warning layer: using 1,2-distearoyl-sn-phosphocholine, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine, cholesterol, and an indicator to prepare lipid vesicles containing an indicator; The indicator is coated with an acid-base dependent copolymer of methyl acrylate-methyl methacrylate-methyl acrylate; Spraying lipid vesicles on one side of the absorption layer; spraying methyl acrylate-methyl methacrylate-methyl acrylate coated with an indicator on the other opposite side of the absorption layer to form a warning layer; S4, preparing capillaries: preparing a perforation die, the perforation die comprising a bottom plate and a plurality of capillary needle rods, the capillary needle rods being vertically distributed on the bottom plate; using the capillary needle rods of the perforation die to penetrate the warning layer, the absorption layer, and the electric field layer from one side of the warning layer to form capillaries, so that the bottom plate of the perforation die is closely attached to the warning layer; S5, preparing an oxygen-carrying layer: dispersing oxygen-containing perfluorocarbon in a fibrinogen solution to prepare a solution B, wherein the oxygen-containing perfluorocarbon is in the form of microspheres in the solution B; Solution B and thrombin solution are sprayed and condensed on the wafer substrate and the capillary needle rod of the perforation mold at the same time, and fibrin gel is formed on the wafer substrate and the capillary needle rod. Oxygen-containing perfluorocarbon microspheres are fixed in the fibrin gel to form an oxygen-carrying layer. The fibrin gel on the surface of the oxygen-carrying layer is in the form of loose pores and capillary columns. The perforated mold is removed to form a hollow capillary column, which together with the capillary pores constitutes a capillary transmission channel; the capillary transmission channel runs through the warning layer, the absorption layer, the electric field layer, and the oxygen carrying layer; S6, preparing the wound surface layer: adding plasmin and fibronectin to the fibrinogen solution to prepare solution C; then spraying the thrombin solution and solution C onto the oxygen-carrying layer simultaneously by spray drying, so that the thrombin, fibrinogen, plasmin and fibronectin are in the form of dry loose bodies in the oxygen-carrying layer; removing the dry loose bodies at the top of the hollow capillary column to make the capillary transmission channel unobstructed, and preparing the initial dressing product; S7, packaging and sterilization: After the initial dressing is packaged, it is sterilized by gamma ray radiation to produce the finished dressing.
2. The preparation method according to claim 1, characterized in that: The thickness of the polarized polyolefin fiber layer is 10 microns to 25 microns, and the electric field strength is -3.0×10 -9 Coulomb / square centimeter~-2.0×10 -9 Coulomb / square centimeter; the thickness of the metal conductive layer is 10 microns to 20 microns.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the polyacrylic acid 974P to the nanocellulose is 1:3 to 1:
10.
4. The preparation method according to claim 3, characterized in that: The mass ratio of DSPC in the lipid vesicles is 78%, the mass ratio of DSPE is 2%, and the mass ratio of cholesterol is 20%.
5. The preparation method according to claim 4, characterized in that: The volume ratio of the oxygen-containing perfluorocarbon to the fibrinogen solution is 0.3:1 to 1:1; the protein content of the fibrinogen solution is 80 mg / ml to 120 mg / ml.
6. The preparation method according to claim 5, characterized in that: The thrombin solution has a titer of 500 IU / ml to 2000 IU / ml.
7. The preparation method according to claim 6, characterized in that: The solution C contains 5ug / ml to 20ug / ml plasmin; the solution C contains 8mg / ml to 12mg / ml fibronectin; the protein content of the fibrinogen solution is 80mg / ml to 120mg / ml; the titer of the thrombin solution is 500IU / ml to 2000IU / ml.
8. A hydrophilic fiber dressing for preventing wound adhesion, characterized in that: The dressing is made according to the preparation method of claim 1.
Citation Information
Patent Citations
Polyionic liquid-coated bacterial cellulose diaphragm and preparation method thereof
CN108232085A
Wound healing patch composition as well as preparation method and application thereof
CN113712733A